The Population-based Impact of Adjuvant Chemotherapy on Outcomes in T2N0M0 Non–Small Cell Lung Cancer. (July 2020) - Arora, Rahul K.; Gibson, Amanda W.; Bebb, D. Gwyn; Cheung, Winson Y.
Abstract : Objectives: The value of adjuvant chemotherapy in T2N0M0 non–small-cell lung cancer (NSCLC) is unclear. Some current guidelines suggest adjuvant chemotherapy be considered for patients with tumors ≥4 cm. Prior population-based evaluations lacked lung cancer-specific survival (LCSS) and health insurance status. The authors aimed to identify predictors of adjuvant chemotherapy use and assess its real-world benefit in T2N0M0 NSCLC. Materials and Methods: The authors included patients who underwent surgery for T2N0M0 NSCLC in a large Canadian province with universal health care between 2004 and 2015, grouping cases by adjuvant chemotherapy receipt. They identified predictors of chemotherapy use with logistic regression and correlates of overall survival (OS) and LCSS using Cox regression. Results: The authors analyzed 967 patients. The median age was 68 years (interquartile range, 61 to 74), 455 (47%) were men, and 164 (17%) received adjuvant chemotherapy. Sex, tumor location, and laterality were similar between groups. Younger age, lower Charlson comorbidity score, large cell histology, and tumor size ≥4 cm were associated with a higher likelihood of chemotherapy receipt (all P <0.05). In the entire cohort and in the ≥4 and ≥5 cm subgroups, chemotherapy improved OS but not LCSS on univariate analysis. Chemotherapy was not associated with OS or LCSS in multivariate analysis (OS hazard ratio [HR], 0.925; 95% confidence interval [0.693-1.236], P =0.598, 0.725 [0.454-1.157], P =0.177 in the ≥4 cm group; LCSS HR, 1.196 [0.843-1.695], P =0.316, 0.917 [0.533-1.577], P =0.754 in the ≥4 cm group). Conclusion: Adjuvant chemotherapy was not associated with improved survival in this population-based T2N0M0 NSCLC cohort, even for ≥4 or ≥5 cm tumors, suggesting that it has a limited role in real-world practice.